MEWUJUDKAN LINGKUNGAN BELAJAR YANG BERSIH DAN AMAN SECARA FISIK SERTA BEBAS DARI PERILAKU BULLYING DI MI HASYIM ASY’ARI - Arif Budijanto; Nurul Firda Oktavia; Ema Yulianty Rahakbau; Kristianus Novris Woli; Apolinaris Pia; Wilhelmina Rangga Bela; Ningsi Melania Mone; Mega Salsal Bella; Ahmad Zidane Kamil; Sevi Pridiyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
An optimal learning environment demands a balance between physical cleanliness and social safety. Based on a needs assessment at MI Hasyim Asy'ari, it was found that some students were not consistently disposing of trash properly and washing their hands with soap, and there was still teasing behavior that could potentially develop into bullying. This community service program aims to improve clean living behavior and prevent bullying through the Knowledge, Skill, Attitude (KSA) approach. The activity was carried out over three days using interactive lectures, discussions, waste sorting and handwashing practices, as well as case study-based psychoeducation and simulations of responses to bullying situations. The results of the activity showed an increase in students' understanding of waste classification and correct handwashing procedures, the development of skills in responding assertively to bullying, and the emergence of empathy towards peers. This program contributes to strengthening a physically healthy and socially safe learning environment as a foundation for student character development, promoting sustainable behavioral change and fostering positive school climate improvement. Furthermore, the program encourages collaborative responsibility among students and teachers in maintaining hygiene standards and nurturing respectful, supportive peer interactions within the school community.